Response of intestinal microbiota to saline-alkaline water in mud crab (Scylla paramamosain) based on multiple low salinity culture modes - Niu, Mingming; Li, Xudong; Chen, Yuhao; Qin, Kangxiang; Liang, Guoling; Hu, Yun; Jiang, Xiaosong; Wang, Huan; Zhu, Ritong; Wang, Chunlin; Mu, Changkao (Frontiers in Marine Science, 2023)
Introduction The intestinal microbiota acts as an additional “organ” that performs a variety of fu\nctions for the host’s health. However, the composition and role of the intestinal microbiota in Scylla paramamosain cultivated in inland low salinity saline-alkaline water are unknown. Methods Accordingly, from the perspective of practical production, we explored the intestinal microbiota communities and the critical bacteria of S. paramamosain in normal salinity seawater (NS), coastal low salinity seawater (CS), acute low salinity seawater (AS) and inland low salinity saline-alkaline water (IS). Results Results showed that there were significant differences in the diversity composition of intestinal microbiota and the relative abundance of dominant taxa in each group of cultured crabs. Firmicutes, Proteobacteria, Bacteroidota and Campilobacterota were shown to be the major phyla shared by the four groups, with Bacteroidota having the highest relative abundance (27.10%) in the inland low salinity saline-alkaline water group (IS). Fusobacteriota had the highest proportion in IS group compared with other low salinity groups. A total of 284 indicator bacteria were identified, belonging to eight phyla, and their relative abundances were varied significantly (P < 0.05). Genus Carboxylicivirga, as the indicator bacterium of the IS group, may play a critical role in the adaptation of crab to saline-alkaline water environment. Moreover, salinity may exert considerable selective pressure on the entire microbial community. Discussion These findings revealed the features of the intestinal microbiome in S. paramamosain in multiple low salinity patterns, and provided candidate probiotics and basic information for crab farming in saline-alkaline water, which was conducive to the development and perfection of mud crab culturing technology in inland low salinity saline-alkaline water.